A Review on Employee’s Health Monitoring System using IOT - Ch. N. Santhosh Kumar, Dr; Mohammed Ali Hussain, Dr (International Journal of Engineering and Technology, 2018)
Due to the automation trends going on rapidly on these days in major organizations employees are constantly facing severe stress regarding their jobs. This insecurity levels in them is leading to several health problems some of which are to be monitored and proper medical care should be taken. Due to the work stress and lack of leisureâ€™s time many Employeeâ€™s are postponing their health check-ups and facing major health issues. These health issues like blood pressure , heart diseases , diabetes, pneumonia etc., can be kept at checking levels if they are regularly monitored and avoiding future problems. Due to these health problems employees are not able to do their work as expected. So if the organizations take a major initiative regarding in this point of view by keeping a regular check on employees health and there routine medical check-ups by sending periodic alert messages to the corresponding employee reminding about their check-ups. In this Paper we are trying to design a software Application which enables the organization to provide necessary health check-up facilities to their employeeâ€™s by collecting the medical information from each employee while joining the organization. It can also track employee health condition during his travel by using GPS. It would be of a great help to every employee. The organization collects medical information regarding the employeeâ€™s making it mandatory process and storing the data in database (PHR), Â Â